Personalidad y suicidio en adultos de Latinoamerica: Revisión Sistemática - Ureña Vera, Anggheles Mishel (2024)
Personality is stable, but it adapts and changes in response to different circumstances and experiences, it is a set of unique psychological characteristics, traits and patterns of behavior that determine the way a person thinks, feels and behaves, there are personality traits that can influence over time to increase vulnerability to suicidal thoughts and behaviors. That is why this research work establishes the prevalence of personality traits that are associated with the manifestation of suicide in adults in Latin America. The methodology used was a systematic review, with a non-experimental cross-sectional design, with a mixed approach, of a deductive type, it is important to mention that selection criteria were established for the collection of information published in different databases, such as: Dialnet, Scielo, Science Direct, Redalyc and Elsevier during the period 2014-2024, delimiting a sample of 23 articles on personality and suicide. As a result, there is evidence of scientific production of the influence of personality on suicide, which according to the processing of the information it is established that the borderline personality trait is related so that the individual has behaviors that affect the making of hasty decisions; that one of the countries with the highest production of scientific evidence is Colombia. In addition, an informative guide was designed with clear and unique information about personality traits, strategies and prevention on suicide in adults. Finally, it is evident that there is a relationship between personality traits and the consummated act, because the interaction between personality traits, mental disorders such as depression, psychosocial problems, creates a complex panorama that increases vulnerability to this phenomenon